PUBLIC PERCEPTION OF ASPECTS AFFECTING WASTE BANK PERFORMANCE - Udin Erawanto; Miranu Triantoro; Nita Sutanti (Universitas Islam Balitar, 2023)
The aim of the research is to find out the aspects that influence the performance of the waste bank in dealing with waste. The source of the research data was 125 customers of the garbage bank in the Kauman sub-district. Data collection techniques using observation and questionnaires. The data analysis uses percentages. The results of the study: the main aspects that affect the performance of the waste bank are the management of the waste bank 121 (97%), the second is provision of garbage collection services 108 (86%), the third is the socialization of the existence of a waste bank 94 (75%), the fourth is economic and social benefits 89 ( 71%), the fifth is the availability of trash carts 25 (20%), and the sixth trash can facility is 15 (12%).